Enhancing Ethanol Production by Fermentation Using Saccharomyces cereviseae under Vacuum Condition in Batch Operation - Abdullah Abdullah; Dessy Ariyanti (International Journal of Renewable Energy Development, 2012)
Ethanol is one of renewable energy, which considered being an excellent alternativeclean-burning fuel to replaced gasoline. In fact, the application of ethanol as fuel still blended withgasoline. The advantages of using ethanol as fuel are that the raw material mostly from renewableresources and the product has low emission which means environmental friendly. Ethanol can beproduced by fermentation of sugars (glucose/fructose). The constraint in the ethanol fermentationbatch or continuous process is the ethanol product inhibition. Inhibition in ethanol productivityand cell growth can be overcome by taking the product continuously from the fermentor. Theprocess can be done by using a vacuum fermentation. The objective of this research is toinvestigate the effect of pressure and glucose concentration in ethanol fermentation. The researchwas conducted in laboratory scale and batch process. Equipment consists of fermentor withvacuum system. The observed responses were dried cells of yeast, concentration of glucose, andconcentration of ethanol. Observations were made every 4 hours during a day of experiment. Theresults show that the formation of ethanol has a growth-associated product characteristic undervacuum operation. Vacuum condition can increase the cell formation productivity and the ethanolformation, as it is compared with fermentation under atmospheric condition. The maximum cellsproductivity and ethanol formation in batch operation under vacuum condition was reached at166.6 mmHg of pressure. The maximum numbers of cells and ethanol formation was reached at141.2 mm Hg of pressure. High initial glucose concentration significantly can affect the productivityand the yield of ethanol.